Preparing for life after university : the Youth Convention Programme 2023 / Nur Ilianis Adnan, Nur Husna Serip Mohamad & Noor Azli Affendy Lee - Adnan, Nur Ilianis; Serip Mohamad, Nur Husna; Affendy Lee, Noor Azli (Academy of Language Studies, 2023)
On January 7th, 2023, UiTMCPP's English Language club hosted a special virtual event named the Youth Convention Programme 2023. The event was live-streamed on the club's YouTube page and aimed to provide final year university students with valuable exposure from exceptional individuals in the industry. The former president of the club, Syed Amir Haikal bin Syed Hisham Alwi, and the newly elected club president, Nuralia Qistina binti Mohd Fadzlul Azim, acted as the hosts for the event. The event showcased three invited speakers: Arinah Najwa, Charissa Ong Ty, and Zack Shah. Each speaker presented their unique perspectives and experiences on the theme of life after university. Arinah Najwa, a senior analyst at BowerGroupAsia, discussed the importance of youth empowerment in the workforce towards nation-building. Charissa Ong Ty, the author of the bestselling book Midnight Monologues, as well as a poet and designer, shared her insights during a session titled "The Journey of Following Your Passion." Finally, Zack Shah, a UiTM alumnus and a copywriter at Nuren Group (Enlinea Sdn Bhd), talked about how UiTM instills valuable working skills in their graduates. The full-day event provided the audience with numerous ideas and insights to empower them in decision-making and to make better choices after graduation. The event was a culmination of past talk shows hosted by Syed Amir Haikal during his tenure in the club, namely Night Talks from April to July 2021, What's Up World from October 2021 to January 2022, and the International Youth Engagement Talk Series in May 2022. The hope is that events like these will not just expose students to the working world, but also encourage them to think about developing skills and knowledge through the opportunities provided